A Rarely Case: Toxic Hepatitis Related Using of Cetirizine - Yavaşoğlu, İrfan; Coskun, Adil; Yaşa, Hadi; Yükselen, Vahit (Fırat University, 2005)
It is known that drug-inducted toxic hepatitis can be developed. In this article, we report a case of a patient who developed hepatitis after receiving cetirizine and reviewed literature.©2005, Fırat Üniversitesi, Tıp Fakültesi

İlaçlara bağlı toksik hepatit geliştiği bilinmektedir. Bu makalede setirizin alımından sonra gelişen bir toksik hepatit olgusu sunularak literatür gözden geçirildi.©2005, Fırat Üniversitesi, Tıp Fakültesi
Nadir Bir Olgu: Setirizin Kullanımına Bağlı Toksik Hepatit